Iron Overload Estimation by Oral Exfoliative Cytology in Beta Thalassemia Major Patients Undergoing Repeated Blood Transfusion - Anaam Mahdi Hadi1 Layla Sabri Yas1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
?-Thalassemia major patients require regular blood transfusion therapy lifelong this lead to iron overload in the body tissues, which is a major cause of morbidity and mortality in these patients. Exfoliative cytology, a non-invasive and inexpensive technique based on microscopic evaluation of epithelial cells after a procedure of their fixation and staining. The aims and objectives of this study were: 1.To estimate iron overload by oral exfoliative cytology using Perl’s Prussian blue stain in ?-thalassemia major patients. 2. To correlate perl’s Prussian blue staining positivity with their serum ferritin levels. Smears were obtained from buccal mucosa of 60 ?-thalassemia major patients (who had taken ?10 transfusions) and 30 healthy subjects of the same age group (5-26) year. Smears were stained with Perl’s Prussian blue stain kit. Blood samples were taken from the study and control group at the same time for estimation of serum ferritin levels. Grading criteria were defined for assessing the Prussian blue positivity. Perl’s positivity was observed in 48 out of 60 of thalassemic patients (80%), with a positive correlation to serum ferritin levels. Perl’s Prussian blue staining of exfoliated cells from buccal mucosa can be used to assess iron overload in ?-thalassemia major patients, as a screening tool.